Recruitment methods for screening programmes: trial of a new method within a regional osteoporosis study. Issue 6845 (11th July 1992) - Garton, M. J.; Torgerson, D. J.; Donaldson, C.; Russell, I. T.; Reid, D. M.
Abstract : OBJECTIVE--To estimate the response rates and operating costs of three recruitment methods within a regional osteoporosis screening programme. DESIGN--Randomised trial of three types of invitation letter: one offering fixed appointments with option to change time, one offering fixed appointments but requiring telephoned confirmation of intention to attend, and one inviting recipient to telephone to make an appointment. SETTING--Osteoporosis screening unit, Aberdeen. SUBJECTS--1200 women aged 45-49 years living within 32 km of Aberdeen and randomly selected from the community health index. 400 women were randomised to each appointment method. MAIN OUTCOME MEASURES--Numbers attending for screening; default rate among women who confirmed appointments; social class of attenders; cost per appointment slot and per completed scan. RESULTS--299 (75%), 277 (69%), and 217 (54%) women were scanned after fixed, confirmable, and open invitations respectively. Women who attended were given a questionnaire, and 694 (87.5%) returned it. No significant differences were found in the social class of attenders among the three methods. Of the 514 women who made or confirmed appointments, 494 attended for a scan. Total costs per scan were 25.00 pounds, 21.40 pounds, and 21.00 pounds for fixed, confirmable, and open invitations respectively. CONCLUSIONS--The offer of a fixed appointment requiring telephoned confirmation has the potential to reduce the costs of scanning without exaggerating any social bias or significantly reducing response rates provided that empty appointments can be rebooked at short notice.